A multi-country investigation of influenza vaccine coverage in pregnant individuals, 2010–2016. Issue 52 (20th December 2021) - Irving, Stephanie A.; Ball, Sarah W.; Booth, Stephanie M.; Regan, Annette K.; Naleway, Allison L.; Buchan, Sarah A.; Katz, Mark A.; Effler, Paul V.; Svenson, Lawrence W.; Kwong, Jeffrey C.; Feldman, Becca S.; Klein, Nicola P.; et al.
Highlights: The World Health Organization prioritizes influenza vaccination for pregnant individuals. Multi-country, multi-season influenza vaccine coverage assessments are sparce. We examined influenza vaccine coverage among pregnant individuals in four countries over ten influenza seasons. Abstract: Background: Many countries recommend influenza vaccination during pregnancy. Despite this recommendation, influenza vaccine among pregnant individuals remains under-utilized and uptake varies by country. Factors associated with influenza vaccine uptake during pregnancy may also vary across countries. Methods: As members of the Pregnancy Influenza Vaccine Effectiveness Network (PREVENT), five sites from four countries (Australia, Canada, Israel, and the United States) retrospectively identified cohorts of individuals aged 18–50 years who were pregnant during pre-defined influenza seasons. Influenza vaccine coverage estimates were calculated for the 2010–11 through 2015–16 northern hemisphere and the 2012 through 2015 southern hemisphere influenza seasons, by site. Sites used electronic health records, administrative data, and immunization registries to collect information on pregnancy, health history, demographics, and vaccination status. Each season, vaccination coverage was calculated as the percentage of individuals who received influenza vaccine among the individuals in the cohort that season. Characteristics were compared between those vaccinated and unvaccinated, by site. Results: More than two million pregnancies were identified over the study period. Influenza vaccination coverage ranged from 5% to 58% across sites and seasons. Coverage increased consistently over the study period at three of the five sites (Western Australia, Alberta, and Israel), and was highest in all seasons at the United States study site (39–58%). Associations with vaccination varied by country and across seasons; where available, parity >0, presence of a high-risk medical condition, and urban residence were consistently associated with increased likelihood of vaccination. Conclusions: Though increasing, uptake of influenza vaccine among pregnant individuals remains lower than recommended. Coverage varied substantially by country, suggesting an ongoing need for targeted strategies to improve influenza vaccine uptake in this population.